Rancang bangun net portabel pembelajaran bola voli difabel - Prasetiya, Danis; Topo Yono; Ahmad Sulaiman (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2025)
One of the most important components of volleyball is the net. The net serves as a boundary for the playing area and determines the height at which the ball must pass. Volleyball nets generally have inflexible heights and designs, making the learning process difficult for students with disabilities, such as those in wheelchairs or individuals with limited mobility. This condition can decrease learning motivation, reduce active engagement, and even pose safety risks if not properly adapted. Innovation in the design of a portable net is a relevant solution to overcome these obstacles. Portable nets allow for height and width adjustments as needed, are easily transported, and can be installed in various locations, both indoors and outdoors. Furthermore, the lightweight yet sturdy materials and construction will support mobility and safety, making volleyball learning for people with disabilities more inclusive and effective. This study uses a Research and Development (R&D) approach to design and test a portable net prototype as a volleyball learning tool for students with disabilities. The R&D method was chosen because it is suitable for producing innovative educational products, from planning, manufacturing, to feasibility testing. In general, the research stages include observation, interviews and design plans. The design research for a portable net as a volleyball learning tool for students with disabilities produces a product in the form of a portable volleyball net that can be adjusted in height, is lightweight, and easy to move so that it supports the inclusive learning process for students. The final product is a portable volleyball net for students with disabilities. It is lightweight, easy to move, and easy to adjust in height, safe and durable, with a feasibility level of >90% according to experts and users, proven to increase the participation and motivation of students with disabilities in volleyball learning, these results indicate that the design of a portable net has succeeded in meeting the needs of inclusive, practical, and effective volleyball learning tools for students with disabilities.